Maximum effect with minimum impact: A new selective control strategy for the Browsing ant Lepisiota frauenfeldi (Formicidae: Formicinae) minimize the impact on non-target species - Masashi Yoshimura; Mayuko Suwabe; Kazuki Tsuji; Yosuke Baba; Hiroshi Kakazu; Tatsuya Miyagi; Masako Ogasawara; Jumpei Uematsu; Evan P. Economo; Koji Ono (PLoS ONE, 2025)
Early-stage control of invasive ants provides an opportunity to suppress establishment while conserving existing biodiversity. We developed and tested a selective control strategy targeting the Browsing ant Lepisiota frauenfeldi , an emerging omnivorous, polygynous, and polydomous invader, during its initial establishment in an urban area of Okinawa Island, Japan. Because the local ant community was still present when the invasion was detected, the trial aimed at reducing the competitive advantage of the target species while preserving biotic resistance from resident species. We hypothesized that weakening L . frauenfeldi through selective chemical treatment would allow existing species to occupy its vacant niches, thereby accelerating eradication. Species-specific baits were formulated using a growth regulator with protein- and carbohydrate-based substrates. Baits were placed near nest entrances identified through monthly surveys over an area of approximately 1.6 hectares. Ant community dynamics were monitored for 44 months using hand-collection and sticky-trap surveys. The invasive ant showed a strong negative response to treatment, with an estimated 92% reduction in occurrence probability, ultimately disappearing from the treated area. Several non-target ant species increased in frequency, consistent with expectation of the niche reoccupation, while most other species remained stable, indicating minimal impact on the broader community. Compared to conventional methods, this approach used drastically less chemical while achieving high efficacy. Implementation through cross-organizational collaboration enabled parallel treatment in adjacent restricted areas and contributed to the program’s success. These results highlight the practical and ecological value of nest-targeted, community-collaborative selective baiting as a strategy for managing omnivorous invasive ants during early establishment.